Positive thinking: an Islamic perspective - Machouche, Salah; Bensaid, Benaouda; Grine, Fadila (IIUM, 2012)
The subject of positive thinking is gaining growing popularity while drawing the increasingly piqued interests of academic researchers and health professionals. The most relevant literature to the topic however, appears to overlook major differences in the religious and cultural beliefs of various nations. In an attempt to fill this lacuna in the cultural and religious dimensions of positive thought, the current research seeks to explore the nature of positive thinking in light of Islamic sources. It sheds light on the structure, order, and parameters of positive thinking according to Muslim beliefs and practices while also highlighting the process of sustaining positive thinking according to Islamic teachings. Using a comparative method of analysis, the current inquiry contrasts both positive and negative thinking patterns in an attempt to determine the influence of religious thought and practice in shaping and sustaining healthy thinking patterns. The research reveals the distinct character and system of positive thinking according to Muslims and suggests new areas of potential interest to psychologists and professional therapists, in the field of sustaining positive thinking among Muslims as well as in multi-cultural societies.